Epidemiological Aspects of Exotic Malaria and Dengue Fever in Travelers in Korea - Park, Sang-Hee (Elmer Press, 2011)
In order to compare the epidemiological aspects of exotic malaria (EM) and dengue fever (DF) imported by travelers in Korea, we have analyzed the current state both of the disease incidence and related risk factors. A total of 345 cases of EM occurred between 2001 and 2008 in Korea, and the average incidence rate per 100,000 population was 0.091. A total of 252 of DF cases occurred during the same period, and its rate was 0.063. While most of the EM and DF prevalence occurred in summer, prevalence in spring and winter was more prominent for EM (P < 0.05 ~ P < 0.01), while outbreaks in summer were more frequent for DF (P < 0.01). In Korea, more males were infected with EM and DF than females (P < 0.01). The remarkable difference between gender distributions in Korea is believed to reflect cultural differences in terms of work and travel. In both diseases, the manhood age bracket (20 - 39 years old) is possible due to increased oversea activities and travel. Moreover, reported EM cases in several prefectures in the regions of Asia and Africa were widely spread by the appropriate vector of mosquitoes, while the vectors of DF in the region of Asia are limited. KEYWORDS: Epidemiology; Exotic malaria; Dengue fever; Traveler; Korea